Success Factors for Humanitarian Access: Quantitative Case Studies of ICRC Visits to Detainees - Futsuki, Kouta; Sekiyama, Takashi (Frontiers in Political Science, 2022)
The importance of humanitarian access has been widely recognized by practitioners and scholars. Nevertheless, factors behind its success have been not yet fully clear. This study, therefore, conducted a quantitative analysis of the ICRC’s detainee visit to elucidate the success factors of humanitarian access. It analyzed a government’s attributes that grants the ICRC access and the ICRC's engagements to soften the government’s refusal of its access. The results revealed the following findings: (1) a government’s capacity is required to an extent to keep public services in armed conflict; (2) material incentive in a government is working, and the ICRC’s assistance for civilians is effective; (3) conceptual incentive to seek the legitimacy is irrelevant; (4) conceptual disincentive to avoid disclosure of the government’s violation of humanitarian norms is working, and a high-level meeting with the ICRC is a little likely to lessen the government’s concern. These findings supplement insights of previous research on general humanitarian access in a quantitative way, implying the possibilities and the limits of humanitarian agency’s engagements. Further research on various types of humanitarian success can clarify its success factors in a more specific way.